Erratum: Hu et al. Numerical Investigation of Flow and Heat Transfer in a Rotor-Stator Cavity with Centripetal Carbon Dioxide Through-Flow. Energies 2019, 12, 2613 - Bo Hu (MDPI AG, 2021)
The authors would like to make the following explanations and changes to the original paper [...]